INDONESIAN MUSLIM WOMEN VOICES OF DOMESTIC VIOLENCE (A Reflection from Hadis Perspective) - Siti Aisyah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
This article deals with hadis perspective on Indonesian muslim women voices of domestic violence. It is found that domestic violence do happen in Indonesia. A number of factors contributing to domestic violence are challenging men’s power and authority which include advising men to adhere to religious and cultural values and norms such as abstaining from alcohol, not having affairs, seeking employment, responding to a man’s anger or accusation during an argument. Women’s attempt to guide men or to negotiate with them seem to undermine men and threaten their designated position in the family ascribed by society. Other factors are infidelity in marriage and polygamy, gender division of labour, financial issues and alcohol. Domestic violence is not justifiable even in the Qur’an.